Micro-lending for small farmers in Bangladesh: does it affect farm households' land allocation decision? - Rashid, Shahidur; Sharma, Manohar; Zeller, Manfred (Project MUSE, 2004)
Despite higher profitability of High Yielding Varieties (HYVs), it has long been hypothesized that lack of access to credit is one of the main reasons, why farmers in developing countries continue to allocate a portion of their land to traditional crop varieties. The empirical testing of this hypothesis has generated a large body of literature with differing conclusions. This paper re-examines the issue in the context of a specially designed group based lending programs for small farmers in Bangladesh, who neither have access to formal sources of credit nor do they qualify to become members of other micro-credit organizations. Two measures of access to credit, credit limit and amount borrowed at a given point in time, have been used to analyze the determinants of farm households' land allocation decision. Under a variety of model specifications, formulated within Heckman's two-step method, the results show that credit limits from the lending programs and informal sources are significant determinants of small farmers' decision to cultivate HYV.